“Optimización en la recuperación de oro, mediante concentración gravimétrica, con el uso de concentradores tipo z, en el Área Minera “San Andrés”, Código: 501417, ubicada en el sector Namirez, parroquia Cumbaratza, cantón Zamora de la provincia de Zamora Chinchipe”. - Domínguez Moreno, Maritza Lorena (2023)
The present research called ❝ Optimization in the recovery of gold, through gravimetric concentration, with the use of type z concentrators, in the mining area ❝San Andrés❞, Code : 501417, located in the Namirez sector, Cumbaratza parish, Zamora canton belonged to the Zamora Chinchipe province ❞, aims to improve the gravimetric recovery process in alluviall mining, due to the fact that there is a recovery of 28.57% , being considered as very low and not profitable enough for the Project. The activities began with the characterization of the mineralized material, for which sampling was carried out and later its properties such as density and granulometry were determined, later laboratory analyzes were carried out in order to know the grades that the gravel possesses. Then, the characteristics of alluvial gold were detemined through direct observation and the plating method. The determination of the flow rate, angle of inclination the type Z concentrator, and the type of carpets continued. Finally, the proposal for the recovery method was elaborated. In the same way, it was identified that there is 36% of fine gold and 64% of coarse gold, reaching the conclusión that the problema in the low recovery of gold lies in the use of blankets that the company currently uses, which is why it is proposed to change this type of carpet to a type of synthetic carpet or where appropriate, jute so that a higher percentage can be trapped. In the same way, the use of a Knelson concentrator for the recovery of fines is proposed, which allows recovering up to 90 % whose equivalent is 0.126 gr/ ton. Key Word: Mineral deposits, alluvial placers, gold recovery, gravimetric concentration.